Art as contemplative practice expressive pathways to the self - Franklin, Michael A. 1956- (SUNY Press, 2017)
"Drawing upon his personal experience as a practitioner-researcher, visual artist, and cancer survivor, Michael A. Franklin offers a rich and thought-provoking guide to art as contemplative practice. His firsthand experience and original artwork complement this extensive discussion by consulting various practice traditions including yoga, rasa and darshan experiences, imaginal intelligence, and the contemplative instincts of select early twentieth-century artists. From this synthesis, Franklin suggests that we treat art as a form of yoga and meditation with the potential to awaken deeper insight into the fundamental nature of the Self. Exercises and rubrics are included that offer accessible instruction for any artist, meditation or yoga practitioner, art educator, or art therapist."--Provided by publisher.